2013
DOI: 10.1021/bi301369b
|View full text |Cite
|
Sign up to set email alerts
|

Interconverting Conformations of Slipped-DNA Junctions Formed by Trinucleotide Repeats Affect Repair Outcome

Abstract: Expansions of (CTG)·(CAG) repeated DNAs are the mutagenic cause of 14 neurological diseases, likely arising through the formation and processing of slipped-strand DNAs. These transient intermediates of repeat length mutations are formed by out-of-register mispairing of repeat units on complementary strands. The three-way slipped-DNA junction, at which the excess repeats slip out from the duplex, is a poorly understood feature common to these mutagenic intermediates. Here, we reveal that slipped junctions can a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 61 publications
2
35
0
Order By: Relevance
“…Wrinkled DNA structures appear transiently in the atomistic simulations, prior to the formation of denaturation bubbles. The DESIGNED sequence, which contains repetitive elements, was uniquely observed to relieve torsional stress through slip defects, which are implicated in genetic diversity in prokaryotes and diseases such as cancer in humans (47). Most strikingly, both the atomistic and coarse-grained DNA simulations show ‘cooperative kinking’, in which defects preferentially occur at opposite sides of the circle due to DNA bending.…”
Section: Resultsmentioning
confidence: 99%
“…Wrinkled DNA structures appear transiently in the atomistic simulations, prior to the formation of denaturation bubbles. The DESIGNED sequence, which contains repetitive elements, was uniquely observed to relieve torsional stress through slip defects, which are implicated in genetic diversity in prokaryotes and diseases such as cancer in humans (47). Most strikingly, both the atomistic and coarse-grained DNA simulations show ‘cooperative kinking’, in which defects preferentially occur at opposite sides of the circle due to DNA bending.…”
Section: Resultsmentioning
confidence: 99%
“…This difference is likely related to the propensity of (CNG) n sequences to form secondary structures once they have slipped and are single stranded owing to the inherent complementarity of the C's and G's within the repeat sequence (Castel et al 2010;McMurray 2010) and to the manner in which Msh2-Msh3 interacts with these unique structures (Lang et al 2011). As the tract length increases, the potential complexity of the secondary structure increases (Gacy and McMurray 1998;Pearson and Sinden 1998;Slean et al 2013). Nonetheless, loss of MSH2 or MSH3 leads to a significant decrease in expansion events in mouse models of HD (Manley et al 1999; Owen et al 2005) and MD1 (van den Broek et al 2002;Foiry et al 2006).…”
mentioning
confidence: 99%
“…A survey of the human genome reference sequence revealed that it harbors more than 32,000 tracts of trinucleotide repeat sequences composed of six or more repeated units (Axford et al 2013). In human exons, which account for less than 3% of the genomic sequence, there are as many as 1,030 trinucleotiderepeat tracts (Slean et al 2013). Polymorphic trinucleotide repeats are better tolerated than dinucleotide and tetranucleotide repeats in translated sequences because their length variation does not change the open reading frame (Panigrahi et al 2012).…”
Section: Discussionmentioning
confidence: 99%